Key proteins of invadopodia are overexpressed in oral squamous cell carcinoma suggesting an important role of MT1-MMP in the tumoral progression - Geovanni Pereira Mitre; Karolyny Martins Balbinot; André Luis Ribeiro Ribeiro; Maria Sueli da Silva Kataoka; Sérgio de Melo Alves Júnior; João de Jesus Viana Pinheiro (BMC, 2021)
Abstract Background Oral squamous cell carcinoma (OSCC) is the most relevant malignant neoplasm among all head and neck tumours due to its high prevalence and unfavourable prognosis. Tumour invasion and metastasis that affect prognosis are result of a set of complex events that cells with invasive potential use to spread to other regions. These cells use several mechanisms to invade tissues, including a type of finger-like membrane protrusion called invadopodia. This study aims to investigate the immunoexpression of invaopodia related-proteins TKs5, cortactin, TKs4 and MT1-MMP in OSCC and correlate it to clinicopathological data. Methods An immunohistochemical evaluation of fifty cases of OSCCs and 20 cases of oral mucosa (OM) were assessed. The expression of invadopodia proteins were analysed in comparison to normal tissue (OM) and correlated to different clinical-stage and histological grade of OSCC. Results TKs5, cortactin, TKs4 and MT1-MMP were significantly overexpressed in OSCC when compared to OM (p < 0.0001). Among tumour stages, TKs5 showed a statistical difference in immunolabelling between stage I and III (p = 0.026). Cortactin immunolabelling was statistically higher in grade I than in grade II and III. No differences were seen on TKs4 expression based on tumour staging or grading. MT1-MMP was higher expressed and showed statistical difference between stages I and III and grades I compared to II and III. Conclusions The invadopodia related-proteins were found to be overexpressed in OSCC when compared to OM, suggesting invadopodia formation and activity. Besides overexpressed in OSCC, cortactin, TKs4 and TKs5 showed no or ambiguous differences in protein expression when compared among clinical-stages or histological grades groups. Conversely, the expression of MT1-MMP increased in advanced stages and less differentiated tumours, suggesting MT1-MMP expression as a promising prognostic marker in OSCC.